2014
DOI: 10.3346/jkms.2014.29.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Diffuse Large B-Cell Lymphoma: An Evaluation of Different Staging Systems

Abstract: The gastrointestinal tract is the most common primary extranodal site for diffuse large B-cell lymphoma (DLBCL). However, there is no consensus on the most appropriate staging system for intestinal DLBCL. We evaluated the utility of the modified Ann Arbor system, the Lugano system, and the Paris staging system (a modification of the Tumor, Node, Metastases [TNM] staging for epithelial tumors) in 66 cases of resected intestinal DLBCL. The cases were treated with surgery, plus either cyclophosphamide, doxorubici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 22 publications
1
30
0
Order By: Relevance
“…Incidence of PGI NHL was higher in women than in men (male:female ratio: 8:9), which was not consistent with previous studies. [5,6] This is likely due to small number of patients included in present study.…”
Section: Discussionmentioning
confidence: 91%
“…Incidence of PGI NHL was higher in women than in men (male:female ratio: 8:9), which was not consistent with previous studies. [5,6] This is likely due to small number of patients included in present study.…”
Section: Discussionmentioning
confidence: 91%
“…These discordances can be attributed to the differences between the various treatment protocols. For example, more than half (60.7 %) of the patients with intestinal involvement in our current cohort underwent a resection of an intestinal lymphoma prior to chemotherapy, a treatment known to be effective in improving the patient outcome [25,26]. In addition, the relatively younger age of our cohort (median age, 55 years) may result in the alteration of survival analysis results and may cause these discordances.…”
Section: Discussionmentioning
confidence: 68%
“…Also, the majority of authors concluded that the initial management with surgery followed by adjuvant chemotherapy resulted in the best overall survival. 4,11,[25][26][27] Meanwhile, surgical resection is beneficial to prevent spontaneous perforation and/or hemorrhage during chemotherapy or radiotherapy, also to relieve symptoms and for accurate diagnosis and staging of the disease.…”
Section: Discussionmentioning
confidence: 99%